(untitled) (World Science, 2020)
The need to develop a system of rehabilitation programs for various stages of medical care providing to children with type 1 diabetes mellitus (DM) is due to a significant increase in the number of children with diabetes mellitus (DM) in recent times, a severe course of the disease, insufficient effectiveness of treatment and the absence of out-of-hospital rehabilitation of children’s patients. Further development of rehabilitation programs for children and adolescents with Type 1 diabetes, basic awareness of the patient and his family regarding the disease and treatment methods is required. Despite the fact that a significant number of scientific studies are devoted to the problems of DM, there are difficulties in introducing an existing innovative product due to its isolation, diversity, organizational and other barriers in the process of transfer to real clinical practice.